The Experience of Emancipation in the Process of Writing M.A. Thesis - Piechowska, Martyna (INSTED: Interdisciplinary Studies in Education & Society, 2019)
The aim of this article is to show the dualism of studying in the frames of an institution situated in neoliberal culture influenced by commercialized ways of thinking, which demands staying in the opposition with the idea of schole. This text is an autoethnographical reflection of a pedagogy student, who sets herself in noninstrumental ways of thinking about education presented amongst others by Gert Biesta, Jan Masschelein, Tyson Lewis and Piotr Zamojski. This article is also an attempt to get back voice which was lost under the regime of directives, norms and guidelines in the era of academic capitalism. Besides, it is also an attempt to take the responsibility of studying into one?s own hands and to experience educational freedom.